An Experimental Study on Concrete Strength Using Egg Shell Powder (ESP) as Partial Replacement of Cement - Tie, Ivy Mei Wen; Mohammad Azmi, Mohamad Azim; Maridan, Nadia Qasrina; Mohd Ramdzam, Muhammad Syawal Hafizuddin (Multidisciplinary Applied Research and Innovation, 2022)
The emission of Carbon Dioxide (CO2) into the atmosphere becomes one of the most common issues that is discussed within the construction industry. Concrete as the most common materials used in construction had contributed the most CO2   emission compared with other building materials. As the solution to reduce the negative impacts of CO2 on the environment, cement is been replaced partially by eggshell powder (ESP). The objective of this study are study the workability of concrete with ESP and determine the effect of ESP toward density and compressive strength development in concrete. In this study, cement was replaced partially by ESP by 5%, 10%, and 15% to investigate the compressive strength of the concrete with ESP as an addictive concrete mix. The samples were divided into 4 types according to the percentage of the ESP replacement with cement which are no replacement, 5%,10%, and 15%. The concrete was tested by compressive strength test according to BS EN 12390-2: 2009 / BS EN 12390-3: 2009. The result compressive strength of the OPC-ESP concrete was decreased in this study.